La nutrición infantil en la jornada escolar y su incidencia en los aprendizajes de los niños de inicial II de la Unidad Educativa Moderna, cantón Milagro año lectivo 2015-2016 - Rizzo León, Tania Vanessa (2016)
During the stage of preschool, children tend to prefer unhealthy foods because they are easily accessible to them and that is why schools within your daily routine include lunch time but, What would happen if the child lacks an adequate nutrition and this situation would affect them in their learning? Proper nutrition is a key element to the biological, psychological, social and motor development of a child, in the first five years we must start educating about healthy eating. But it is unfortunate as certain institutions and parents have no knowledge of the importance of the nutrients infants need to perform daily activities in preschool. Poor nutrition can cause: drowsiness, fatigue, dehydration, obesity and malnutrition…..